Learning from incidents in medically assisted reproduction: the Notify Library as a learning tool. Issue 4 (October 2021) - Alteri, Alessandra; Petrisli, Evangelia; Nolan, Paula; Pisaturo, Valerio; Fehily, Deirdre; Navarro, Aurora; Strong, D Michael; Cardillo, Massimo; Costa, Mauro
Abstract: Biovigilance is the systematic monitoring of serious adverse reactions and events (SARE) that ensures the quality and safety of tissues and cells for human application in medically assisted reproduction (MAR). The Notify Library is an open access database launched by the World Health Organization and supported by the Italian National Transplant Centre (CNT) that has collected information on documented adverse occurrences in transplantation, transfusion and MAR. It is not a SARE register, but rather a collection of SARE types identified primarily by review of published articles and case reports from national or regional vigilance programmes. The Notify Library includes many well-documented records of adverse occurrences in MAR treatment, representing a useful tool for MAR operators in the evaluation of the risks associated with the clinical application of reproductive tissues and cells. It is updated with new records when a new type of incident is reported for the first time. All incident types described might have teaching value during the risk management carried out by a MAR centre. Sharing lessons learned from these incidents represents an important didactic opportunity that can help MAR centres to improve their processes and to achieve higher standards of quality and safety.